Photo Chemical Hydrogen Generation from Orthorhombic CaFe2O4 Nanoparticles Synthesized by Different Methods. Issue 8 (21st March 2017) - Dom, Rekha; Kim, Hyun Gyu; Borse, Pramod H.
Abstract: CaFe2 O4 (CFO) nanoparticles with the orthorhombic phase were synthesized using solid state reaction (SSR), polymer complex (PC), microwave sintering (μW) and self‐propagating combustion (SPC) methods. Hydrogen (H2 ) evolution by photocatalytic water splitting (WS), over these nanoparticles have been investigated and compared. Their crystallinity, surface area, and band energetics have been studied. It reveals that the CFO synthesized by SSR, PC, μW methods exhibit high crystallinity than that obtained in SPC. The μW synthesized CFO photocatalysts (PHC) exhibited better optical properties than those obtained using conventional SSR route, though they took <60 times less preparation time than SSR. The optical and electrochemical measurements indicate that the CFO shows suited band energetic for H2 generation by WS. In particular, the CFO PHCs obtained from μW method are most efficient &display an order high quantum yield (1.57 %) than others. Electrodes fabricated from μW sintered PHC exhibited low electrochemical charge transfer resistance (CTR) than others yielding high efficiency. Abstract : An orthorhombic phase eco‐friendly ferrite photocatalyst (PHC) is synthesized and studied in‐depth. The computational study indicates CaFe2 O4 as a suited system for photocatalytic H2 generation, and is experimentally validated here. The ferrite system is synthesized by various methods to achieve efficient PHC by virtue of properties as crystallinity, opto‐electronic properties etc . The PHC prepared by microwave sintering method exhibits maximum efficiency with quantum yield of 1.57 % for H2 generation. It is found to be best PHC for pollutant degradation under sunlight .